Edukasi Pentingnya 1000 HPK dalam Pencegahan Gangguan Tumbuh Kembang Anak di Kampung KB Rawa Makmur Bengkulu - Rahmawati, Reza; Handayani, Dian; Romdani, Ayu Nadiyah Permatasari; Salsabila, Fazira; Elena, Felicitas; Salsabila, Frisya Nutia; Amanda, Savira Intan (UNIB Press, 2024)
The First 1000 Days of Life is a period of 270 days (nine months) in the womb plus the first 730 days (two years) of a child's life. The first 1,000 days of life are important because this is a period of growth and development for children who are in a risky period. This community service aims to find out the level of understanding of teenagers and women, especially pregnant women, about the importance of nutrition for children's growth and development and minimizing unwanted diseases that occur in children in KB Rawa Makmur Village RT 12 RW 01. This community service is Community Service, community description, using audio (visual) methods, using instruments in the form of questionnaires (pre-test and post-test). A total of 30 respondents in this community service were residents of KB Rawa Makmur Village RT 12 RW 01, Bengkulu City. The results of this percentage show that there is progress or advancement in the knowledge that has been obtained by mothers and young women in Rawa Makmur KB Village, Bengkulu City. The conclusion from this activity is that education and counseling can increase knowledge in the community about the importance of the first 1000 days of life for children.